Donor Age and Red Cell Age Contribute to the Variance in Lorrca Indices in Healthy Donors for Next Generation Ektacytometry: A Pilot Study - van Cromvoirt, Ankie M.; Fenk, Simone; Sadafi, Ario; Melnikova, Elizaveta V.; Lagutkin, Denis A.; Dey, Kuntal; Petrushanko, Irina Yu.; Hegemann, Inga; Goede, Jeroen S.; Bogdanova, Anna (Frontiers in Physiology, 2021)
The ability of red blood cells (RBCs) to transport gases, their lifespan as well as their rheological properties invariable depend on the deformability, hydration, and membrane stability of these cells which can be measured by Laser optical rotational red cell analyser (Lorrca® Maxsis, RR Mechatronics). The osmoscan mode of Lorrca is currently used in diagnosis of rare anemias in clinical laboratories. However, a broad range of normal values for healthy subjects reduces the sensitivity of this method for diagnosis of mild disease phenotype. In this pilot study, we explored the impact of age and gender of 45 heathy donors, as well as RBC age on the Lorrca indices. Whereas gender did not affect the Lorrca indices in our study, the age donors had a profound effect on the O_hyper parameter. To study the impact if RBC on the osmoscan parameters, we have isolated low- (L), medium- (M), or high- (H) density fractions enriched with young, mature and senescent RBCs respectively and evaluated the influence of RBC age-related properties such as density, morphology, and redox state on the osmoscan indices. As before, O_hyper was the most sensitive parameter, dropping markedly with an increase in RBC density and age. Senescence was associated with a decrease in deformability (EI_max) and tolerability to low and high osmolatites (Area). L-fraction was enriched with reticulocytes and cells with high projected area and EMA staining, also contained a small number of cells small in projected area and most likely, terminally senescent. L-fraction- were on average slightly less deformable than mature cells. The cells from the L-fraction produced more oxidants and NO, than all other fractions. However, RBCs from the L-fraction contained maximal levels of reduced thiols compared to other fractions. Our study suggests that reference values for O_hyper should be age-stratified, and, most probably, corrected for the average RBC age. Further multi-center study is required to validate these suggestions before implementing them into clinical practice.